Modification of Manufacturing Carbol with Lemongrass as a Disinfectant - Nandari, Wibiana Wulan; S, Tutik Muji; Puspitasari, Mitha; N, Susanti Rina (RSF Conference Series: Engineering and Technology, 2022)
Carbolic acid is a cleaning fluid or disinfectant that can be used to clean various surfaces, especially floors. Carbolic acid is used to prevent germs and viruses from growing so as to prevent disease and its spread. Most housewives often use chemical-based floor cleaners that are ready-made or more practical. Long-term and too frequent use can be harmful to the body and the environment. Therefore, one solution to minimize this is to use natural ingredients that are already available and developed in Lubuklinggau City, such as lemongrass to be used as carbolic acid. The preparation begins by dissolving the arpus into the NaOH solution until it dissolves, then adding a mixture of pine oil, teepol and propylene glycol until everything is homogeneously mixed. Carbol is ready to use. The resulting product is carbolic floor disinfectant. The results showed that the greater the content of lemongrass essential oil, the greater the inhibition zone, meaning that the greater the amount of lemongrass essential oil added, the Carbol solution would be better for cleaning or killing bacteria, and the better the disinfectant properties.